POLITICAL BEHAVIOUR OF SULTAN HASANUDDIN AND SULTAN NUKU: Islamic Political Perspective - Irwan Abbas; Darmawijaya Darmawijaya; Ajat Sudrajat (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
This study aims to elucidate the political conduct of Sultan Hasanuddin and Sultan Nuku. Sultan Hasanuddin was a legitimate political leader who fought with Dutch forces during the mid-17th century. Sultan Nuku, an opposition leader, lacked significant legitimacy and subsequently engaged in conflict with Dutch forces during the late 18th century. The study employs a critical historical method that utilizes an Islamic political concept approach. This method aims to generate a critical historical explanation that promotes a shift from problematic political conduct that conflicts with human values to developmental political conduct based on human values. This study utilizes the Islamic political concept to conclude that Sultan Hasanuddin's political behaviour is noncompliant with the desired Islamic political behaviour, thus, problematic. Islam instructs political leaders to cultivate constructive political conduct when establishing domestic authority. To secure robust support and loyalty for political decisions, an Islamic leader must cultivate three key political behaviours: safeguarding, guiding, and motivating the populace. Sultan Hasanuddin was not responsible. Sultan Hasanuddin's internal political oppression was a vulnerability during the mid-17th century war against the Dutch in South Sulawesi. The study concludes that Sultan Nuku's political conduct aligns with Islamic political norms and is deemed favourable. Sultan Nuku effectively employed political strategies to govern and inspire his subjects. Historical evidence suggests that Islamic political behaviour aided Sultan Nuku in establishing a strong internal force to resist the Dutch. Sultan Nuku's effective political conduct was instrumental in his triumph over the Dutch in the late 18th century in North Maluku.